Knowledge, Attitude and Practice of Contraceptives among Saudi Women in Aseer Region, Saudi Arabia - Mubashar, H; Almushait, M; Sukit, B; Shaamash, A; Handady, S; Almutawa, N (Bangladesh Journal of Medical Science, 2016)
Objective: The study was carried out to assess the knowledge, attitude towards, and practice of contraception and the factors that could affect its use among Saudi women in Aseer region of Saudi Arabia. Methods: This cross-sectional and hospital-based study was conducted in Aseer Region, Saudi Arabia, during one year (January, 2014 December, 2014). Five-hundred women of reproductive age (1845 year) were interviewed regarding their knowledge, attitude and practices of contraception. The inquiries were recorded by a predesigned questionnaire. Questions on methods of contraception known and source of knowledge and their practices were recorded. Results: The mean ± SD of age was 32.7 + 7.2 years. (99.2%) of women heard and had knowledge of contraception, while (0.8%) said they did not know anything about contraception. (377 subjects, 75.4%) used contraception, while 123 subjects (24.6%) did not. Oral pill method of contraception was the most popular method known and practiced (87.0%, 32.2% respectively). The media seemed to be the major source of information (40.8%). In response to the reason for non-use, the majority said they wanted more children (10.2%). The major reason for the use of contraception was to limit family size (32.0%). The majority (79.6%) of women had good attitude towards contraception. Conclusion: The present study concludes that a significant proportion of respondents have good knowledge about contraception. But practice of contraception and compliance is low. Desire of more children is one of the major factors among reasons of the non-use of contraception. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.430-434